PENGARUH MANAJEMEN KAS TERHADAP LIKUIDITAS PADA PT INTRIAS MANDIRI SEJATI DI KOTA MAKASSAR - Asrul Syam; Hasriani; Jumriani (Paser Institute Of Accounting and Finance, 2023)
The researcher formulated the research problem, namely "How big is the influence of cash management on liquidity at PT Intrias Mandiri in Makassar City?" with the aim of knowing the magnitude of "the influence of cash management on liquidity at PT Intrias Mandiri in Makassar City". In the company PT Intrias Mandiri, which is one of the companies operating in the field of main focus in providing and managing outsourcing of labor, it has done a lot of work on surveys, infrastructure, installation, maintenance, trouble shooting and troubleshooting of telecommunications networks and also does not escape the use of cash in carrying out liquid financial transactions. Cash requires special management called cash management so that the company can run effectively. This aims to avoid the risk of lack of funds and the risk of bankruptcy. in 2004 the percentage level of cash held in the company was 5.14% of current assets. Meanwhile, the liquidity percentage level reached 60.89% of current debt. In 2005 the percentage level of cash in the company was 4.89% of current assets, meaning that in 2005 cash decreased by 0.25%. Meanwhile, the liquidity percentage level reached 75.79%, meaning that in 2005 liquidity increased by 14.9%. In 2006 the percentage level of cash in the company was 6.78% of current assets, meaning that in 2006 cash increased by 1.89%. Meanwhile, in 2006 the liquidity percentage level reached 77.15% of current debt, meaning that in 2006 liquidity increased by 1.36%. The increase in cash which is not in line with the increase in liquidity shows that over the last three years cash management has fluctuated while liquidity has always increased. It appears that in 2005 the level of cash management decreased while the level of liquidity increased, this was because in 2005 there was a decrease in the amount of cash in the company.